Synthesis and characterisation of cobalt oxide nanoparticles decorated graphene oxide and its electrocatalytic behaviour - Usai, Vincent; Mugadza, Tawanda; Chigondo, Fidelis; Shumba, Munyaradzi; Nharingo, Tichaona; Moyo, Mambo; Tshuma, Piwai (Elsevier Ltd, 2021)
Electrocatalytic behaviour of graphene oxide nanosheets (GONS) and cobalt oxide nanoparticles (Co3O4NPs) composite modified glassy carbon based sensor for 2,4 dichlorophenol (2,4 DCP) is investigated in this work. The GONS and Co3O4NPs were successfully synthesised and characterised by Fourier Transform Infrared Red (FTIR) spectroscopy, UV–Vis spectroscopy, Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM) and Energy Dispersive X-ray (EDX) spectroscopy, electrochemical impedance spectroscopy and cyclic voltammetry. The electrode surface area and surface coverage were 0.13 cm2 and 1.31 × 10−12 mol cm−2 respectively after modification with GONS/Co3O4NPs composite. The modified electrode had an electro-oxidation catalytic rate constant, k, of 3.6 × 106 M−1 s−1 and limit of detection of 3.5 × 10−7 M for the same test analyte. The electrode showed good reproducibility and an appreciably low oxidation potential (0.8 V) for 2,4-DCP.